Kejadian infeksi Klamidia trakomatis di serviks dan tuba pada pasien kehamilan ektopik terganggu di RSUP H. Adam Malik Medan dan RS Jejaring FK USU - Hendry Adi S; Henri Salim Siregar; Fidel Gannis Siregar (Fakultas Kedokteran USU, 2013)
Introduction : Chlamydia trachomatis is one of the most common causative agents of sexual transmitting diseases (STD) world wide. Subclinical Chlamydia trachomatis infections on the upper genital tract often emerge due inadequate detetection and early medication, resulting in both acute and chronic infection that would eventually cause ectopic pregancies and inferility. To determine the insidence of cervical and tubal Chlamydia trachomatis infections by means of polymerase chain reaction (PCR) assay methods, the charecteristics of disturbed ectopic pregnancies, the association with both cervical and tubal Chlamydia trachomatis infections in patients diagnosed with disturbed ectopic pregancies at Haji Adam Malik general hospital in Medan and networking hospital of University of North Sumatera medical school.Methods : This research is an observational study with a cross sectional approach conducted on Chlamydia trachomatis patients diagnosed with disturbed ectopic pregnancies.Result : Prevalence rates of cervical and tubal Chlamydia trachomatis infected patients diagnosed with ectopic pregnancies reached 36% (9/25) and 12% (3/25), respectively. Even though these following results are considered statistically irrelevant, history taking and physical examinations concluded a tendency towards an increased risk of Chlamydia trachomatis infections up to 64% in subjects married between 20-35 years old (16 patients out of 25 patients), reaching 72% in patients with confirmed history of leucorrhea (18 out of 25 patients), and 56% in subjects with a confirmed history of genital tract/pelvic infections (14 out of 25 patients).Keywords : ectopic pregnancy; Chlamydia trachomatis; polymerase chain reaction